Application Of Fuzzy Logic In Color Detection Robot Arm Simulator - Rifq Surya Pradhana; Zulfahmi Syahputra; Arpan (International Journal of Economic, Technology and Social Sciences (Injects), 2022)
Robot is one of the important tools in the industry under certain conditions. The world of education itself has done a lot of research in the field of robotics. The robot arm is one of them, the existence of a robot arm is expected to provide a function or performance in accordance with the work of the human arm and has stronger strength. The robot arm that is built applies a fuzzy logic method that determines the color of the object and will be moved according to the predetermined color, the color consists of three colors, namely red, green and blue. Robots are designed to be flexible and easy to use. It has controllers that have to be reprogrammed at any time to suit their function, like the Arduino Uno, and actuators like servomotors that are low-voltage and easy. This is why the TowerPro SG90 Servo motor was chosen to build the robot arm manipulator.